2022
DOI: 10.3390/microorganisms10050935
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rhizosphere Inoculation with Pseudomonas mandelii on Formation of Apoplast Barriers, HvPIP2 Aquaporins and Hydraulic Conductance of Barley

Abstract: Pseudomonas mandelii strain IB-Ki14 has recently been shown to strengthen the apoplastic barriers of salt-stressed plants, which prevents the entry of toxic sodium. It was of interest to find out whether the same effect manifests itself in the absence of salinity and how this affects the hydraulic conductivity of barley plants. Berberine staining confirmed that the bacterial treatment enhanced the deposition of lignin and suberin and formation of Casparian bands in the roots of barley plants. The calculation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…It was suggested that restriction of water flow through the apoplast pathway may be eliminated by an enhancement of the cell-to-cell pathway through the membrane water channels—aquaporins (AQPs) [ 18 ]. In accordance with this suggestion, we demonstrated that bacteria-induced strengthening of the apoplast barriers was accompanied by increased abundance of AQPs in the roots of barley plants [ 19 ]. It was of interest to find out if bacterial inoculation influences the LTP abundance and deposition of suberin and how these effects may be related to AQP activity and hydraulic conductance of pea plants.…”
Section: Introductionsupporting
confidence: 67%
“…It was suggested that restriction of water flow through the apoplast pathway may be eliminated by an enhancement of the cell-to-cell pathway through the membrane water channels—aquaporins (AQPs) [ 18 ]. In accordance with this suggestion, we demonstrated that bacteria-induced strengthening of the apoplast barriers was accompanied by increased abundance of AQPs in the roots of barley plants [ 19 ]. It was of interest to find out if bacterial inoculation influences the LTP abundance and deposition of suberin and how these effects may be related to AQP activity and hydraulic conductance of pea plants.…”
Section: Introductionsupporting
confidence: 67%
“…Nevertheless, considering the concept of plant phenotypic plasticity under harsh environmental conditions [ 82 ], changes in plant microstructure would increase the plant body’s ability to store and circulate water. Among them are the increased plant cell vacuolization, increased water storage specialized cells, and changes in the volume ratio of the apoplastic and symplastic compartments [ 75 , 83 ]. Furthermore, these integrative mechanisms of plant water conservation favor the induction of plant response enzymatic–metabolic machinery related to cell protection and damage restoration (i.e., ROS production associated with biological membranes and biomolecule damage).…”
Section: Stress Tolerance Mechanisms Mediated By Plant Growth-promoti...mentioning
confidence: 99%
“…Thus, bacteria can increase expression of genes encoding aquaporins in maize plants [ 42 ]. Increased aquaporin abundance was recently found in barley plants treated with B. subtilis IB-22 [ 23 ]. Hormone abscisic acid (ABA) is known to increase the activity of aquaporins [ 43 ], and increased ABA concentration was found in barley plants treated with B. subtilis IB-22 [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This problem remained unresolved if the same effect occurred in the absence of salinity, affecting the hydraulic conductivity of plants. Staining with berberine hemisulfate confirmed that bacterial treatments increased the deposition of lignin and suberin and the formation of Casparian bands in roots of barley and pea [ 23 , 24 ]. Calculation of hydraulic conductivity through correlating transpiration to the leaf water potential showed that it did not decrease in plants treated with bacteria.…”
Section: Introductionmentioning
confidence: 99%